Beginning Arduino - McRoberts, Michael (Apress, 2012)
I first discovered the Arduino in 2008 when I was looking for ways to connect temperature sensors to my PC so I could make a Cloud Detector. I wanted to try out a cloud detection concept I’d read about on a weather forum, and as it was experimental, I didn’t want to spend a lot of money on it in case it failed. There were many solutions on the market, but the Arduino appealed to me the most. Not only did it seem to be an easy and cheap way to connect the sensors I required but it could be used for other cool things. Thousands of projects in blogs, video sites, and forums showed the cool things people were doing with their Arduinos. There seemed to be a huge sense of community with everyone trying to help each other.